Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Join our platform to connect with experts ready to provide precise answers to your questions in different areas. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

Rewrite 2x+5y=3 using function notation​

Sagot :

Answer:

Given f(x) = x2 + 3x – 1, find

a) f(1)

b) f(–1)

c) f(a)

d) f(x – 1)

Step-by-step explanation:

a) f(1) = (1)2 + 3(1) – 1 = 3

b) f(–1) = (–1)2 + 3(–1) – 1 = –3

c) f(a) = a2 + 3a – 1

d) f(x – 1) = (x – 1)2 + 3(x – 1) – 1

= x2 – 2x + 1 + 3x – 3 – 1 = x2 + x –3

We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.